The prognostic role of metformin in patients with endometrial cancer: a retrospective study. (August 2016) - Seebacher, Veronika; Bergmeister, Birgit; Grimm, Christoph; Koelbl, Heinz; Reinthaller, Alexander; Polterauer, Stephan
Abstract: Objective: Metformin has recently been discussed to possess anticancer activities and to positively affect the risk of developing cancer. We performed the present study to investigate the association of metformin and survival in patients with endometrial cancer. Study design: Within the present study we retrospectively reviewed the records of 465 consecutive patients with endometrial cancer. Drug intake of metformin was correlated with clinico-pathological parameters and the patients' survival. Chi-square test, Kruskal Wallis test, the product limit method of Kaplan and Meier, and multivariable Cox regression models were used to assess associations between metformin and clinico-pathological parameters and survival, as appropriate. Results: Eighty-seven (18.7%) patients suffered from diabetes and of these 46 (52.8%) used metformin at the time of diagnosis. When analysing all patients, metformin did not affect the patients' survival. However, within the subgroup of overweight patients metformin was associated with a prolongation of overall survival ( p  = 0.04). Within this subgroup, diabetic patients who did not use metformin had a 2.3 times higher risk for death (95%CI 1.1–4.7; p  = 0.02) compared to non-diabetic patients and diabetic patients using metformin. Metformin was not associated with prolonged recurrence-free or cancer-specific survival, irrespective of the patients' body mass index ( p  = 0.08 and p  = 0.4, respectively). Conclusion: The results of our study might suggest a beneficial effect of metformin on overall survival in overweight diabetic patients with endometrial cancer. However, the question, if metformin can reduce the risk to die from endometrial cancer or improves all cause mortality only still remains open and needs further investigation.